2014
DOI: 10.1089/thy.2013.0448
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Immunoglobulin G4 Levels in Patients with Graves' Disease and Their Clinical Implications

Abstract: A small portion of GD patients harbored elevated serum IgG4 levels. They were older, had increased hypoechoic areas in the thyroid, and appeared to be responsive or prone to be hypothyroid after ATD treatment. Thus, the present study suggests the presence of a novel subtype of GD. Measuring serum IgG4 levels may help to distinguish this new entity and provide potential therapeutic options for GD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
47
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 26 publications
10
47
0
2
Order By: Relevance
“…Thus, patient background differed between the studies. An association between IgG4 thyroiditis and male predominance or diffuse hypoechogenicity has also been suggested in other reports [7,14]. Consistent with those studies, ultrasonography revealed that hypoechoic areas were larger in the elevated IgG4 group than in the non-elevated IgG4 group in our prospective study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, patient background differed between the studies. An association between IgG4 thyroiditis and male predominance or diffuse hypoechogenicity has also been suggested in other reports [7,14]. Consistent with those studies, ultrasonography revealed that hypoechoic areas were larger in the elevated IgG4 group than in the non-elevated IgG4 group in our prospective study.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with the diagnostic criteria for IgG4-RD, patients 4 and 5 probably had extra-thyroid at the maximum position [7,13].…”
Section: Clinical Features Of Six Patients With Elevated Serum Igg4 Lmentioning
confidence: 54%
See 1 more Smart Citation
“…It is believed to occur equally among males and females [1,2]. Recent reports have also suggested that a small fraction of Graves' disease patients also have elevated IgG4 levels with some features suggestive of IgG4TD [21,22]. Takeshima K et al reported that 6.4% of 109 patients with Graves' disease had elevated IgG4 titres [21].…”
Section: Igg4 Related Thyroid Disease (Igg4rtd)mentioning
confidence: 99%
“…An association between thyroid diseases such as Graves' disease, Hashimioto's thyroiditis, and RT and IgG4-related disease (IgG4-RD) has recently been reported [11][12][13][14][15]. Patients with IgG4-RD exhibit elevated serum IgG4 levels, IgG4-positive plasma cells, and tissue fibrosis and organ dysfunction caused by lymphocyte infiltration into multiple organs [16,17].…”
mentioning
confidence: 99%